2018
DOI: 10.21037/apm.2017.08.08
|View full text |Cite
|
Sign up to set email alerts
|

Meditational spiritual intercession and recovery from disease in palliative care: a literature review

Abstract: Human body is a biological, open system and maintains itself in the changing environment. Disease state is cured by many medicinal systems for healing. Esoteric healing (through introspective hypnosis, meditation and spiritual intercession) is the system where its believers regard Supreme Being as Omnipotent, Omnipresent and Omniscient. Such persons take ill health as a boon and pray through meditation that He may by His Mercy grant health or if God wishes otherwise, they happily accept it so that they keep mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…9,15,[24][25][26] The moderate correlation between these two types of instruments means they should not be substituted for each other. The variables driving this nonsubstitutable character may include respondents' age, treatment type (eg, radiation vs chemotherapy), 15 types of vocal dysfunctions, 25 socioeconomic status and social support, 23 cross-cultural differences and individual cultural backgrounds, 34 and speech modes. In terms of the latter, it should be noted that prior studies by Kasper et al, 24 Portone et al, 25 and Dehqan et al, 26 all of whose participants were laryngeal, reported strong correlations between scores on the VHI and V-RQOL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,15,[24][25][26] The moderate correlation between these two types of instruments means they should not be substituted for each other. The variables driving this nonsubstitutable character may include respondents' age, treatment type (eg, radiation vs chemotherapy), 15 types of vocal dysfunctions, 25 socioeconomic status and social support, 23 cross-cultural differences and individual cultural backgrounds, 34 and speech modes. In terms of the latter, it should be noted that prior studies by Kasper et al, 24 Portone et al, 25 and Dehqan et al, 26 all of whose participants were laryngeal, reported strong correlations between scores on the VHI and V-RQOL.…”
Section: Discussionmentioning
confidence: 99%
“…7 In the absence of such alternatives, the VHI, VHI-10, and V-RQOL—all of which are voice-related measures—are often adopted to assess the impact of voice problems on alaryngeal patients. 10–23…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Quality Of Life (QOL) is also considered as an important indicator of treatment outcome for cancer therapies. 3,4 Despite constantly advancing treatment protocols, improvement in Quality of life of head and neck cancer patients is still a challenge in most circumstances. In developing countries like India there are very few studies on the QOL in head and neck cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research on yoga for palliative care has shown improvements in the sleep quality, mood, stress, management of physical symptoms, and overall quality of life. 2 , 3 , 4 Palliative potential of home-based yoga sessions in women with advanced cancer was evaluated in a study. 2 Enhanced mind-body and body-spirit connections, benefits at physical, mental, and emotional level as well as the alleviation of illness impacts were observed.…”
mentioning
confidence: 99%